Given:
[tex]\begin{gathered} y=3x+19\ldots\ldots\ldots(1) \\ y=5x+33\ldots\ldots\ldots(2) \end{gathered}[/tex]To solve: The system of equations by substitution
Explanation:
Substituting equation (1) in equation (2), we get
[tex]\begin{gathered} 3x+19=5x+33 \\ 3x-5x=33-19 \\ -2x=14 \\ x=-7 \end{gathered}[/tex]Substitute the x value in equation (1), we get
[tex]\begin{gathered} y=3(-7)+19 \\ y=-21+19 \\ y=-2 \end{gathered}[/tex]Final answers: The solutions are,
[tex]\begin{gathered} x=-7 \\ y=-2 \end{gathered}[/tex]